Wellness tourism experience and destination brand love - Kim, Sung in; Al-Ansi, Amr; Lee, Jin-Soo; Chua, Bee-Lia; Phucharoen, Chayanon; Han, Heesup (Routledge, 2024)
This study assessed various aspects of the wellness tourism experience in Thailand. A survey was conducted with a sample of 420 Chinese tourists. The findings revealed significant and insignificant effects of the wellness tourism experience on the development of destination brand love. Additionally, it confirmed that barriers and destination familiarity play a vital role in shaping tourists’ responses and strengthening their affinity towards the destination brand. The results highlight tourists’ focus on comprehensive experiences rather than external dynamics like weather. This study suggests collaboration among stakeholders to enrich the overall travel experience and prioritize the emotional wellbeing of tourists.